(untitled) (Bangladesh Journal of Botany, 2024)
This study was envisaged to explore the variation characteristics of Ormosia henryi Prain leaves from four different areas of Hunan provenance of China based on analyzing the geometric morphologic information of the leaf. Specifically, the leaf morphological indices were firstly calculated, and multiple comparison analysis, canonical analysis of the principal coordinates and fisher linear discriminant model were employed to decipher the morphological variability based on contour outlines. The results showed that the leaf morphological indices exhibited significant differences between the samples of different areas. Variability also exists between the Ormosia henryi of four areas of the provenance. The results provide a theoretical basis for the study of genetic diversity and genetic improvement of Ormosia henryi. Bangladesh J. Bot. 53(3): 773-781, 2024 (September) Special